A catalytic filler and its preparation method and application

By combining active components such as cobalt oxide, zinc oxide, copper oxide and manganese oxide on the alumina support, catalytic fillers are solved, and the existing electrocatalytic materials have been effectively achieved, with high efficiency, strong adaptability and no secondary pollution.

CN116078397BActive Publication Date: 2025-03-28HUNAN LIANGYOU ENVIRONMENTAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310045766.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-30
Publication Date
2025-03-28
Estimated Expiration
2043-01-30

AI Technical Summary

Technical Problem

The existing electrocatalytic materials have poor adaptability and low catalytic efficiency, and may lead to the release of iron ions and cause secondary pollution.

Method used

Catalytic fillers are prepared by combining the aluminum oxide support with active components such as cobalt oxide, zinc oxide, copper oxide and manganese oxide. The oxidation performance is enhanced by electrocatalytic release of hydroxyl radicals.

Benefits of technology

The adaptability and catalytic efficiency of catalytic fillers are improved, secondary pollution is avoided, and power consumption is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004055344170000081
    Figure BDA0004055344170000081
Patent Text Reader

Abstract

The present invention belongs to the technical field of sewage treatment, and specifically relates to a catalytic filler and a preparation method and application thereof. The catalytic filler provided by the present invention comprises an alumina carrier and an active component, wherein the active component comprises a first active component and a second active component; the first active component is cobalt oxide and zinc oxide; the second active component is selected from at least one of copper oxide, manganese oxide, and sodium composite salt. The present invention obtains a catalytic filler by compounding an alumina carrier and the active component, which has strong adaptability, high electron transfer rate, reduced power consumption, high catalytic efficiency, and no secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sewage treatment, and in particular relates to a catalytic filler and a preparation method and application thereof. Background Art

[0002] In recent years, new business formats and technological upgrades, such as the new energy vehicle industry, fine chemicals, pesticides, smelting and other industries, while meeting production standards, have generated industrial wastewater with high concentrations, strong toxicity, and high heavy metal content. Under conventional wastewater treatment processes, treatment is difficult, costly, emissions fail to meet standards, and efficiency is low.

[0003] Advanced oxidation process: mainly refers to the production of strong oxidizing substances with hydroxyl radical ·OH as the core in the strong oxidation process, which can quickly, non-selectively and thoroughly oxidize various pollutants in the environment. Advanced oxidation processes include Fenton oxidation, ozone oxidation, wet oxidation, electrochemical oxidation, photocatalytic oxidation, sonochemical oxidation, etc. These methods all mention the generation of ·OH, which is a common feature of these methods and an important reaction in advanced oxidation processes, but the way of producing ·OH is different. ·OH is an oxidant with extremely strong oxidizing ability, its redox potential is extremely high, and its oxidizing property is non-selective. It can react with almost any substance in water and is widely used.

[0004] Electrochemical catalytic oxidation is a common method among many advanced oxidation technologies. It uses the basic principle of electrolysis to remove pollutants. When electrolysis occurs, sewage serves as the electrolyte, and pollutants in the sewage serve as electrolytes. Through the electrolysis process, oxidation and reduction reactions occur at the positive and negative electrodes, respectively. On the other hand, the hydroxyl radicals generated during electrolysis are used to convert pollutants into harmless substances to purify sewage. However, the electron transfer rate of existing two-dimensional electrocatalytic materials is low, which results in high power consumption and low catalytic efficiency. At the same time, some iron-carbon catalysts will release iron ions, leading to secondary pollution of wastewater. In addition, existing catalytic materials have poor adaptability and cannot be used for changes in wastewater quality caused by changes in weather and environment, technological process updates in industrial production, etc. Summary of the invention

[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing electrocatalytic materials such as poor adaptability, low catalytic efficiency, release of iron ions, and secondary pollution, thereby providing a catalytic filler and a preparation method and application thereof.

[0006] The present invention provides a catalytic filler, comprising an alumina carrier and an active component, wherein the active component comprises a first active component and a second active component;

[0007] The first active component is cobalt oxide and zinc oxide;

[0008] The second active component is selected from at least one of copper oxide, manganese oxide and sodium composite salt.

[0009] The present invention does not specifically limit the oxide forms of cobalt oxide, zinc oxide, copper oxide and manganese oxide. For example, manganese oxide can be in the form of manganese oxide, trimanganese tetraoxide, manganese dioxide, dimanganese trioxide, etc.

[0010] The Al2O3 carrier used in the present invention is a standard product with the grade A-AS-04 and a particle size of 3-12 mm.

[0011] Preferably, the active component accounts for 1-10% of the mass of the alumina carrier;

[0012] And / or, the molar ratio of the metal element in the first active component to the metal element in the second active component is (1-4):(1-6).

[0013] Preferably, the active components are cobalt oxide, zinc oxide and manganese oxide;

[0014] And / or, the molar ratio of Co, Zn and Mn elements in the cobalt oxide, zinc oxide and manganese oxide is (1-2): (1-2): (1-2).

[0015] Preferably, the active components are cobalt oxide, zinc oxide and copper oxide;

[0016] And / or, the molar ratio of Co, Zn and Cu elements in the cobalt oxide, zinc oxide and copper oxide is (1-2): (1-2): (1-2).

[0017] Preferably, the active component is a composite salt of cobalt oxide, zinc oxide, manganese oxide and sodium;

[0018] And / or, the molar ratio of Co, Zn, Mn and Na elements in the composite salt of cobalt oxide, zinc oxide, manganese oxide and sodium is (1-2): (1-2): (1-2): (1-2).

[0019] Preferably, the active components are cobalt oxide, zinc oxide, manganese oxide and copper oxide;

[0020] And / or, the molar ratio of Co, Zn, Mn and Cu elements in the cobalt oxide, zinc oxide, manganese oxide and copper oxide is (1-2): (1-2): (1-2): (1-2).

[0021] The present invention provides a method for preparing the above-mentioned catalytic filler, comprising the following steps:

[0022] The carrier is immersed in a soluble salt solution corresponding to the active component, dehydrated and sintered to obtain the catalytic filler.

[0023] Preferably, the immersion time is 3-4h;

[0024] And / or, the dehydration temperature is 90-105°C, the dehydration time is 2-3h, and the dehydration heating rate is 5-10°C / min;

[0025] And / or, the sintering temperature is 500-1000°C, the sintering time is 4-8h, and the sintering heating rate is 5-10°C / min.

[0026] Preferably, the soluble salt in the soluble salt solution is an acid ion salt; typically, but not limiting, the soluble salt can be a carbonate or a sulfate;

[0027] And / or, the total mass concentration of soluble salts in the soluble salt solution is 8%-10%;

[0028] And / or, the mass ratio of the soluble salt solution to the carrier is (0.3-1):1;

[0029] And / or, after the sintering, the step of natural cooling and cleaning is also included.

[0030] The present invention also provides an application of the above-mentioned catalytic filler or the catalytic filler prepared by the above-mentioned method in electrocatalytic oxidation treatment of wastewater;

[0031] Optionally, the wastewater is organic wastewater, saline wastewater or heavy metal wastewater. The present invention is particularly suitable for the treatment of high-concentration wastewater.

[0032] The technical solution of the present invention has the following advantages:

[0033] (1) The catalytic filler provided by the present invention comprises an alumina carrier and an active component, wherein the active component comprises a first active component and a second active component; the first active component is cobalt oxide and zinc oxide; the second active component is selected from at least one of copper oxide, manganese oxide, and sodium composite salt. The present invention obtains a catalytic filler by compounding an alumina carrier and three active components, especially cobalt oxide and zinc oxide, which is more conducive to releasing hydroxyl radicals ·OH under the action of electrocatalysis and enhances its oxidation performance. The obtained catalytic filler has strong adaptability, high catalytic efficiency and no secondary pollution.

[0034] (2) The preparation method of the catalytic filler provided by the present invention comprises the following steps: immersing the carrier in a soluble salt solution corresponding to the active component, dehydrating and sintering to obtain the catalytic filler. The present invention can be well loaded with the particle carrier by compounding a stable Al2O3 carrier with a soluble salt solution corresponding to a composite salt of cobalt oxide, zinc oxide, copper oxide, manganese oxide, and sodium, thereby obtaining a catalytic filler with strong adaptability, high catalytic efficiency, and no secondary pollution.

[0035] (3) The catalytic filler provided by the present invention is easy to obtain, low in cost, has a high electron transfer rate, low power consumption, and is pollution-free. DETAILED DESCRIPTION

[0036] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0037] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0038] Example 1

[0039] This embodiment provides a method for preparing a catalytic filler, comprising the following steps:

[0040] 500g Al2O3 carrier (diameter 3-5mm) is immersed in 250g CoSO4, ZnSO4, MnSO4 metal salt solution (the total mass concentration of metal salt in the metal salt solution is 8%, and the molar ratio of Co, Zn and Mn elements is 2:2:1) for 4h. After the impregnation, the Al2O3 carrier is dehydrated and sintered at a dehydration temperature of 105°C, a dehydration time of 2h, a dehydration heating rate of 5°C / min, a sintering temperature of 1000°C, a sintering time of 8h, and a sintering heating rate of 5°C / min to obtain the catalytic filler.

[0041] Example 2

[0042] This embodiment provides a method for preparing a catalytic filler, comprising the following steps:

[0043] 500g Al2O3 carrier (diameter 3-5mm) is immersed in 150g CoSO4, ZnSO4, CuSO4 metal salt solution (the total mass concentration of metal salt is 10%, and the molar ratio of Co, Zn and Cu elements is 2:1:1) for 3h. After the impregnation, the Al2O3 carrier is dehydrated and sintered at a dehydration temperature of 90°C, a dehydration time of 3h, a dehydration heating rate of 10°C / min, a sintering temperature of 800°C, a sintering time of 4h, and a sintering heating rate of 5°C / min to obtain the catalytic filler.

[0044] Example 3

[0045] This embodiment provides a method for preparing a catalytic filler, comprising the following steps:

[0046] 500g Al2O3 carrier (diameter 3-5mm) is immersed in 250g CoSO4, ZnSO4, MnSO4, Na2SO4 metal salt solution (the total mass concentration of the metal salt is 10%, wherein the molar ratio of Co, Zn, Mn and Na elements is 1:2:1:1) for 4h. After the impregnation, the Al2O3 carrier is dehydrated and sintered at a dehydration temperature of 100°C, a dehydration time of 2.5h, a dehydration heating rate of 7°C / min, a sintering temperature of 1000°C, a sintering time of 8h, and a sintering heating rate of 7°C / min to obtain the catalytic filler.

[0047] Example 4

[0048] This embodiment provides a method for preparing a catalytic filler, comprising the following steps:

[0049] 500g Al2O3 carrier (diameter 3-5mm) is impregnated in 250g CoSO4, ZnSO4, MnSO4, CuSO4 metal salt solution (the total mass concentration of the metal salt is 8%, and the molar ratio of Co, Zn, Mn and Cu elements is 1:2:1:1.5) for 4h. After the impregnation, the Al2O3 carrier is dehydrated and sintered at a dehydration temperature of 105°C, a dehydration time of 2h, a dehydration heating rate of 5°C / min, a sintering temperature of 1000°C, a sintering time of 8h, and a sintering heating rate of 5°C / min to obtain the catalytic filler.

[0050] Comparative Example 1

[0051] This comparative example provides a catalytic filler, which only uses Al2O3 carrier as the catalytic filler.

[0052] Comparative Example 2

[0053] This comparative example provides a catalytic filler, which differs from Example 1 in that an equimolar amount of MnSO4 is used instead of ZnSO4, and other conditions are the same.

[0054] Comparative Example 3

[0055] This comparative example provides a catalytic filler, which differs from Example 1 in that an equimolar amount of MnSO4 is used instead of CoSO4, and other conditions are the same.

[0056] Comparative Example 4

[0057] This comparative example provides a catalytic filler, which differs from Example 1 in that an equimolar amount of MnSO4 is used to replace ZnSO4 and CoSO4, and other conditions are the same.

[0058] Comparative Example 5

[0059] This comparative example provides a catalytic filler, which differs from Example 1 in that 250g of metal salt solution of Fe2(SO4)3, CuSO4, and MnSO4 (the total mass concentration of metal salts in the metal salt solution is 8%, and the molar ratio of Fe, Cu and Mn elements is 2:2:1) is used instead of the metal salt solution of CoSO4, ZnSO4, and MnSO4, and other conditions are the same.

[0060] Test Case

[0061] The catalytic device assembled with the catalytic fillers prepared in the embodiment and the comparative example was used to treat wastewater of two concentrations. The electrode had a surface area of ​​1 m 2 The titanium electrode plate is coated with 20 kg of the catalytic filler on the anode surface, and a DC power supply (maximum output power) is passed: 18V 200A, the wastewater flow rate is: 1 cubic meter / hour, the treatment time is 60 minutes, and the chemical oxygen demand, ammonia nitrogen content and total phosphorus content of the wastewater before and after treatment are measured to determine the removal effect and adaptability of each catalytic filler on pollutants.

[0062] The chemical oxygen demand in the wastewater was measured according to the HJ 828-2017 standard, the ammonia nitrogen in the wastewater was measured according to the HJ 535-2009 standard, and the total phosphorus in the wastewater was measured according to the HJ 671-2013 standard. The test results are shown in Table 1.

[0063] Table 1

[0064]

[0065] It can be seen from the table that the treatment effect of the embodiments of the present invention on pollutants is significantly better than that of the embodiment without filler and other fillers in the comparative example. The chemical oxygen demand generally reflects the degree of pollution of the wastewater. The higher the oxygen demand, the higher the degree of pollution. The wastewater after electrocatalytic treatment with the catalytic filler prepared in the embodiment of the present invention, whether it is high-concentration wastewater 1 or medium- and low-concentration wastewater 2, has a significantly reduced oxygen demand, indicating that the catalytic filler of the present invention has strong adaptability and high catalytic efficiency.

[0066] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A catalytic filler for electrocatalytic oxidation is used in the electrocatalytic oxidation treatment of wastewater, characterized in that: The catalytic filler of the electrocatalytic oxidation is composed of an alumina carrier and an active component, wherein the active component is composed of a first active component and a second active component; The first active component is cobalt oxide and zinc oxide; The second active component is selected from at least one of copper oxide, manganese oxide, and sodium composite salt; The active component accounts for 1-10% of the mass of the alumina carrier; The molar ratio of the metal element in the first active component to the metal element in the second active component is (1-4):(1-6).

2. The use of the catalytic filler for electrocatalytic oxidation according to claim 1 in electrocatalytic oxidation treatment of wastewater, characterized in that: The active components are cobalt oxide, zinc oxide and manganese oxide; And / or, the molar ratio of Co, Zn and Mn elements in the cobalt oxide, zinc oxide and manganese oxide is (1-2): (1-2): (1-2).

3. The use of the catalytic filler for electrocatalytic oxidation according to claim 1 in electrocatalytic oxidation treatment of wastewater, characterized in that: The active components are cobalt oxide, zinc oxide and copper oxide; And / or, the molar ratio of Co, Zn and Cu elements in the cobalt oxide, zinc oxide and copper oxide is (1-2): (1-2): (1-2).

4. The use of the catalytic filler for electrocatalytic oxidation according to claim 1 in electrocatalytic oxidation treatment of wastewater, characterized in that: The active component is a composite salt of cobalt oxide, zinc oxide, manganese oxide and sodium; And / or, the molar ratio of Co, Zn, Mn and Na elements in the composite salt of cobalt oxide, zinc oxide, manganese oxide and sodium is (1-2): (1-2): (1-2): (1-2).

5. The use of the catalytic filler for electrocatalytic oxidation according to claim 1 in electrocatalytic oxidation treatment of wastewater, characterized in that: The active components are cobalt oxide, zinc oxide, manganese oxide and copper oxide; And / or, the molar ratio of Co, Zn, Mn and Cu elements in the cobalt oxide, zinc oxide, manganese oxide and copper oxide is (1-2): (1-2): (1-2): (1-2).

6. Use of the catalytic filler for electrocatalytic oxidation according to any one of claims 1 to 5 in electrocatalytic oxidation treatment of wastewater, characterized in that: The method for preparing the catalytic filler for electrocatalytic oxidation comprises the following steps: The carrier is immersed in a soluble salt solution corresponding to the active component, dehydrated and sintered to obtain the catalytic filler.

7. The use of the catalytic filler for electrocatalytic oxidation according to claim 6 in electrocatalytic oxidation treatment of wastewater, characterized in that: The immersion time is 3-4h; And / or, the dehydration temperature is 90-105°C, the dehydration time is 2-3h, and the dehydration heating rate is 5-10°C / min; And / or, the sintering temperature is 500-1000°C, the sintering time is 4-8h, and the sintering heating rate is 5-10°C / min.

8. The use of the catalytic filler for electrocatalytic oxidation according to claim 6 in electrocatalytic oxidation treatment of wastewater, characterized in that: The soluble salt in the soluble salt solution is an acid radical ion salt; And / or, the total mass concentration of soluble salts in the soluble salt solution is 8%-10%; And / or, the mass ratio of the soluble salt solution to the carrier is (0.3-1):1; And / or, after the sintering, the step of natural cooling and cleaning is also included.

Citation Information

Patent Citations

  • Ozone catalytic oxidation catalyst for treating reverse osmosis concentrated water and preparation method of catalyst

    CN105618080A

  • Composite catalyst for aid-containing wastewater treatment

    CN110302779A

  • High-activity aluminum oxide three-dimensional electrode particle filler as well as preparation method and application thereof

    CN110902769A